Penitipan Sertipikat Tanah pada Kantor Notaris dalam Pembuatan Akta Pengikatan Jual Beli Tanah di Kota Bukittinggi - Wulan, Sari; Warman, Kurnia; Yoserwan, Yoserwan (Universitas Ekasakti, 2023)
The agreement of sale and purchase made before notaries is commonly referred to as the Deed of Sale and Purchase, hereinafter referred to as PPJB (Perjanjian Pengikatan Jual Beli). PPJB is a temporary agreement made when the conditions for the sale and purchase process are not yet fulfilled. In the practice of notarial deeds, it is common to store land title certificates related to the deed, whether it is Right to Build (Hak Guna Bangunan) or Right of Ownership (Hak Milik). In reality, many parties have ill intentions, leading to cases of reporting notaries for alleged embezzlement of the deposited land certificates. This thesis addresses the following issues: 1) What are the reasons for storing land certificates in the making of Sale and Purchase Deeds in the city of Bukittinggi? 2) What are the responsibilities of notaries regarding the storage of land certificates at the Notary Office in Bukittinggi? 3) What legal protections are available for land certificate holders who have entrusted their certificates to the Notary Office? The research method used in this study is the empirical juridical method, which involves approaching the problem by examining the applicable legal norms and connecting them with the legal facts found in the field. The reasons for depositing certificates at the notary office, especially with Notary Elfita Achtar, are due to the incomplete legal process and the absence of clear and immediate elements in the sale and purchase agreement. The responsibilities of a notary regarding the deposited certificates can be categorized into three types: administrative responsibility, civil responsibility, and criminal responsibility. Legal protection for certificate owners can be sought through administrative means (filing a report with the Notary Supervisory Board), civil means (filing a civil lawsuit with the District Court), and criminal means (submitting a report to the Police Office).